Implementation of the beam-loading effect in the tracking code RF-track based on a power-diffusive model - Olivares Herrador, Javier; Latina, Andrea; Aksoy, Avni; Fuster Martínez, Nuria; Gimeno, Benito; Esperante, Daniel (Frontiers in Physics, 2024)
The need to achieve high energies in particle accelerators is leading to the development of new accelerator technologies, resulting in higher beam intensities and more compact devices with stronger accelerating fields. In such scenarios, Beam Loading effects occur and a intensitydependent gradient reduction affects the accelerated beam as a consequence of its interaction with the surrounding cavity. In this study, a power-diffusive partial differential equation is derived to account for this effect. Its numerical resolution has been implemented in the tracking code RF-Track, allowing the simulation of apparatuses where transient beam loading plays an important role. Finally, measurements of this effect have been carried out in the CLEAR facility at CERN, finding good agreement with the RF-Track simulations.